Activating Social Capital: How Peer and Socio-Emotional Mentoring Facilitate Resilience and Success for Community College Students - Beals, Rebecca; Zimny, Sean; Lyons, Faith; Bobbitt, Olivia (Frontiers in Education, 2021)
This article details the impact of the intensive mentoring model, through faculty-to-student and peer-to-peer mentoring, utilized in WAESO-LSAMP community colleges. We pay particular attention to the practice of socio-emotional mentoring, the development of a “mentoring chain,” and the impact of communities of support on student and faculty participants. Specifically, we discuss how these separate modes of mentoring impact students from underrepresented students in developing and activating social capital, developing collaborative support systems, fostering confidence and self-efficacy, combatting impostor syndrome and stereotype threat, and embracing the importance of failure in the scientific process. Methods and data include qualitative analysis of forty-six in-depth interviews with program participants, including faculty mentors and community college students, at three community college sites within the WAESO-LSAMP alliance. We address specific implications for faculty working with underrepresented STEM community college students and provide evidence of best practices for setting up a community of support that leads to academic and personal success.